Examination of front-of-packaged (FOP) labelling systems and nutrition-health statements on packaged foods in Türkiye - İçyer, Necattin Cihat; Doğan, Hicran (My University, 2024)
There is a growing trend worldwide towards greater awareness of food labelling systems in the fight against global challenges such as unhealthy nutrition and obesity. Nearly 30 governments have approved various front-of-package (FOP) labelling systems, and many countries plan to adopt them. However, since there is no legal regulation regarding FOP labelling systems in Türkiye, nutrition and health-related statements appear on many packaged food products. Although these statements enable consumers to make healthy food choices, they also have the potential to mislead consumers by supporting the perception that foods lacking essential nutritional components or containing potentially harmful substances are healthy. This study examined FOP labelling systems used worldwide, and nutrition and health-related statements on the front of 1336 packaged foods in 6 categories in Türkiye were analysed. Although it varies in each category, the most common expressions are generally recommended daily amount (%14.5), fat (%16), sugar (%9.9), vitamin-mineral (%5.1), and protein (%9.4). Additionally, salt (%0,9), vegan (%2), additive (%11.6) and fibre content (%6.8) information is also commonly declared. As a result, the implementation of effective labeling regulations in Turkey can enhance public health and mitigate the adverse effects of unhealthy nutrition on society.
Keywords: Food security; Food labelling; Front of the package (FOP); Nutrition and health